PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD NEGERI 010 SIALANG MAKMUR KECAMATAN KELAYANG KABUPATEN INDRAGIRI HULU - Zarnuji, Zarnuji; Marhadi, Hendri; Kurniaman, Otang (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Absract: The problem in this research is the low result study of Social scince in Fourth grade students of Elementary School number 010 Sialang Makmur,Kelayang district.The average of daily test value is 62,75, it can be seen from only 6 person from 20 students or 30% that achieve the criteria of passing (KKM) that is 70. For this reason ,the research is done.The purpose of the research is to improve the result of Social science of the Fourth graders of the Sialang makmur,Kelayang district by implementing the coperative type Numbered Heads Together (NHT). With the formulation of study is Can the implementation of learning model type Numbered Heads Together improve the result of Social science subject of the Fourth grade students of Elementary School number 010 Sialang Makmur, Kelayang? The design of study used is class action research that is done in two cycles where every cycle has two meetings and once for daily test with the total number of students is 20 person, 9 girl students and 11 boy students. Data collected are observational data and result data of study.From the analysis of teacher’s activities,in the first cycle meeting 1 the result gotten is 12 (50%) which category is ‘Fair’. In the second meeting the result gotten is 15 (62,5%) which categry is ‘Fair.’And continued at cycle II meeting 4 increase in the result become 20 (83,3%).which category is ‘Good’,and the fifth meeting,the result is increased which score 22 (91,6%) which category ‘Very Good’.From data analysis of sudents’activities meeting 1 cycle I is gotten the score is 12 (50%) which category is ‘Fair”,increased in meeting 2 which score 16 (66,6%) which category is’Fair”. In the cycle II meeting 4 increase become 20 (83,3%) which category’ Good’. Then, in meeting 5 there is increasing in result with the score 23 (95,8%) which category is ‘Very Good’.In the first daily test , there is an increasing result from the basic score 11,1% with the average 69,75.And in the second daily test ,the score increase 37% of the basic score with the average 86,00. From this research, the conclusion is by implementing cooperative model of learning type Numbered Heads Together can increase the result study of Social Science of The Fourth Grade Sudents of Elementary School number 010 Sialang Makmur, Kelayang, Indragiri Hulu RegencyKey word:Numbered Heads Together (NHT), Learning outcomes of Social Class